Visiones de desarrollo en países ricos en recursos naturales - Carrillo Hoyos, Sandra (2017)
This article addresses a global debate around the resource curse theory. Broadresearch demonstrates that some resource rich countries face with major challenges to achieve social welfare, economic stability and sustainable environmental management. Recent evidence emphasizes the relevance of institutions to determine the degree to achieve a better development performance in resource rich countries. This article supports the role of institutions to take advantage of the exploitation of natural resources, particularly those at the local level. The Peruvian context is especially analyzed concerning the challenges to improve the use and management of extractive revenues.